If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = -11x + -1 Reorder the terms: -6 + 5x = -11x + -1 Reorder the terms: -6 + 5x = -1 + -11x Solving -6 + 5x = -1 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -6 + 5x + 11x = -1 + -11x + 11x Combine like terms: 5x + 11x = 16x -6 + 16x = -1 + -11x + 11x Combine like terms: -11x + 11x = 0 -6 + 16x = -1 + 0 -6 + 16x = -1 Add '6' to each side of the equation. -6 + 6 + 16x = -1 + 6 Combine like terms: -6 + 6 = 0 0 + 16x = -1 + 6 16x = -1 + 6 Combine like terms: -1 + 6 = 5 16x = 5 Divide each side by '16'. x = 0.3125 Simplifying x = 0.3125
| 3x+7=-x | | 9v^2+30vw+25w^2=0 | | k=-3+-0.5x | | x^2+18xw+81w^2=0 | | 6+k=10k-9(k+2) | | 5x+3(x+2)=2x-7 | | 3/7x4/6 | | X+x+3x-7+3x-7+3x-7+3x-7=28 | | 3(-x+4)+(-x-8)=10-2x | | (-2)(sinx)=a+cosy | | 81y^2-36xy+4x^2=0 | | 2.4=57 | | -2x=3+5y | | -6x-(2x-12)-36=0 | | 9(2-n)=n-2 | | w/4-4=8 | | 7(2x+9)=-7 | | w+42=-28 | | V=136 | | w+42=w-28 | | f(-x)=3x^2+2x-2 | | 1.5f=16.5 | | 4(-5x+6)=-156 | | ((2.63-8.99)/1.25)-((3.90r-1.77)/2.45)=r | | 1.5+8=88 | | 17-3=6z+5+z+2 | | 5(5-4x)=5 | | 9.04x+3.59(8x-5)=12.03x+0.5614 | | Cot(2x)-2=1 | | 7.3z=7.3 | | 2m+(m-2)+102+(m-2)+115+(m+12)+110= | | 7(x+3)=6(n-3) |